The Academic Experiences of Senior High School Students in the Midst of Pandemic - Jayben, P Locion; Johncarlo C. Sison; Sean Bazel C. Suarez; Meriel T. de Jesus; Jennesa C. Pelande; Maryknoll S. Uy (PT FORMOSA CENDEKIA GLOBAL, 2022)
As the world evolves, new problems arise and this leads to a bigger barrier for students especially with education. This paper uncovers the struggles of students with regards to the new learning modality as a result of the pandemic; COVID-19. It presents and discuss findings and methods in which the researchers examined information acquired from personal interviews – phenomenological study through “thematic analysis” (Sutton & Austin, 2015). Specifically, STEM Students from Samar National School were asked various questions about their experiences with education in the midst of the pandemic. 5 informants were purposively selected through selection criteria and data was collected through a semi-structured interview. As a result, the responses demonstrate how STEM students deal with the pandemic and the challenges it brings. Some students experience barriers especially doing online classes in their own homes; such as noise, doing chores, and lack of motivation. Some are not used to the new learning set-up and they only try their best to adapt with this as soon as possible. Not only with education prior but some also faced mental health struggles as an effect of the change of learning practices. Furthermore, most of the informants have comparable replies to the many issues they have experienced. In sum, the results uncovered the different challenges and struggles that these students faced with the new learning modality and how these affected their performance. This study is also about conveying a message to all students that in this fight, they are not alone.